The memoirs of Allen Oldfather Whipple the man behind the Whipple operation - Whipple, Allen Oldfather, 1881-1963 (Tfm Pub., 2003)
This book is an edited version of Whipple's previously unpublished memories. In these pages the retired Whipple describes the journey of his life from the very beginning in Persia, where he was born, to the very end in New Jersey where he died. He provides snap shots of himself, his family and friends, his colleagues, and the changing times in which he lived.